A tecnologia da informação como instrumento de apoio à controladoria: um estudo de caso envolvendo a aplicação das ferramentas de business intelligence - Reginato, Luciane (Universidade do Vale do Rio do Sinos, 2006)
The information has attributes that added to an appropriate communication to its users qualifies itself as a strategical resource for a company management, given its capability to interfere in the quality of the taken decision, thus claiming for care to its production. This fact justifies the existence of organizational areas specifically responsible for the information treatment as well as for it accuracy and availability, such as the controlling and information technology areas. Thus, the ways these areas have to carry out the mentioned objectives become an important field to be studied. In that sense, this research has investigated the contribution of the tools provided by the Information Technology, specifically those of Business Intelligence (BI), to the controlling area to make easier for it to accomplish its mission of supporting the decision making process with useful information. The study was carried out through a field research, specifically a case study in a company of Diadema-SP, on which the su
Keywords: comunicação; controladoria; dimensões de controle; informação; tecnologia da informação; business intelligence; communication; controlling; dimensions of control; information; information technology; Ciências Sociais Aplicadas